Sevoflurane postconditioning alleviates hypoxia-reoxygenation injury of cardiomyocytes by promoting mitochondrial autophagy through the HIF-1/BNIP3 signaling pathway - Yang, Long (PeerJ, 2019)
BACKGROUND: Sevoflurane postconditioning (SpostC) can alleviate hypoxia-reoxygenation injury of cardiomyocytes; however, the specific mechanism remains unclear. This study aimed to investigate whether SpostC promotes mitochondrial autophagy through the hypoxia-inducible factor-1 (HIF-1)/BCL2/adenovirus E1B 19-kDa-interacting protein 3 (BNIP3) signaling pathway to attenuate hypoxia-reoxygenation injury in cardiomyocytes. METHODS: The H9C2 cardiomyocyte hypoxia/reoxygenation model was established and treated with 2.4% sevoflurane at the beginning of reoxygenation. Cell damage was determined by measuring cell viability, lactate dehydrogenase activity, and apoptosis. Mitochondrial ultrastructural and autophagosomes were observed by transmission electron microscope. Western blotting was used to examine the expression of HIF-1, BNIP3, and Beclin-1 proteins. The effects of BNIP3 on promoting autophagy were determined using interfering RNA technology to silence BNIP3. RESULTS: Hypoxia-reoxygenation injury led to accumulation of autophagosomes in cardiomyocytes, and cell viability was significantly reduced, which seriously damaged cells. Sevoflurane postconditioning could upregulate HIF-1α and BNIP3 protein expression, promote autophagosome clearance, and reduce cell damage. However, these protective effects were inhibited by 2-methoxyestradiol or sinBNIP3. CONCLUSION: Sevoflurane postconditioning can alleviate hypoxia-reoxygenation injury in cardiomyocytes, and this effect may be achieved by promoting mitochondrial autophagy through the HIF-1/BNIP3 signaling pathway.